Effect of thermal regime on fatty acid dynamics in male European eels (Anguilla anguilla) during hormonally-induced spermatogenesis - Baeza Ariño, Rosa; Mazzeo, Ilaria; Vilchez Olivencia, Maria Carmen; Gallego Albiach, Victor; Peñaranda, D.S.; Pérez Igualada, Luz María; Asturiano Nemesio, Juan Francisco (Aquaculture, 2014)
S [EN] Little is known about the role of fat and fatty acids in European eel spermatogenesis. The aim of this research was to study the changes in fat content and to carry out a quantitative analysis of the fatty acid composition of the muscle, liver and gonad of European male eels during hormonally induced sexual maturation. Three different thermal regimes were used (two variable: T10 and T15; and one constant: T20) to replicate the changes in temperature that these fish experience during their transoceanic reproductive migration. Spermatogenesis was reached earlier in treatment T20, suggesting that spermatogenesis in the European eel is closely regulated by water temperature. Although eels lose body mass due to the period of fasting that accompanies gonadal growth, no significant changes were found in the fat and fatty acid content of the muscle during the experimental period. With regard to the liver, the levels of palmitic, eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids increased significantly at the start of the spermiation process in all the thermal treatments. In the testis, levels of EPA, arachidonic acid (ARA) and DHA remained constant during the maturation process whereas the levels of the rest of the fatty acids decreased significantly. The stability of the ARA and EPA levels in the testis may have a physiological significance, whereas the stability of the DHA levels may have a structural significance. The results suggest that the progression of spermiation is influenced by water temperature and demonstrate the importance of EPA, ARA and DHA in European eel reproduction. This study demonstrates that complementary research focusing on the lipid composition of commercial diets could improve the sperm quality of this species. Funded by the European Community's 7th Framework Programme under the Theme 2 "Food, Agriculture and Fisheries, and Biotechnology", grant agreement no. 245257 (PRO-EEL). Victor Gallego, Ilaria Mazzeo and M. Carmen Vilchez had predoctoral grants from the Spanish Ministry of ...